Magnitude and Factors associated with complications of type 2 diabetes: Analysis of a Diabetes Mellitus Surveillance System - Cornetero-Muro, Víctor (2021)
Background: Type 2 diabetes (DT2) complications has been increased the demand for specialized services in Peruvian Social Security(EsSalud), so it is necessary to determine the magnitude and factors associated with chronic complication due to DT2 in this population. Material and Methods: Cross-sectional study based on 7875 patients with DT2≥18 years attended by ambulatory care during 2016-2017, notified in the Diabetes Mellitus Surveillance System of EsSalud. Sociodemographic, clinical and comorbidity variables were evaluated using a bivariate analysis and Poisson regression model with robust variance to determine the prevalence ratio of chronic complication due to DT2. Results: The microvascular complication of DT2 was associated with male sex (PR=1.25; 95% CI:1.10-1.42; p<0.01), HbA1c>9.0% (PR=1.25; 95% CI:1.08-1.46; p<0.01), hypertension (PR=1.30; 95% CI: 1.14-1.49; p<0.01), anemia (PR=1.57; 95% CI: 1.31-1.88; p <0.01), thyroid disease (PR=1.48; 95% CI:1.07-2.03; p=0.02), cancer (PR=1.70; 95% CI: 1.26-2.30; p<0.01) and fatty liver (PR=1.78; 95% CI:1.28-2.48; p<0.01). Receiving education for DT2 self-care showed a negative association with microvascular complication (RR=0.84; 95% CI:0.73-0.96; p<0.01). DT2´s macrovascular complication was associated with male sex (PR=1.52; 95% CI:1.21-1.91; p <0.01), arterial hypertension (PR=2.72; 95% CI:1.90-3.91; p <0.01), anemia (PR=1.98; 95% CI:1.33-2.95; p<0.01) and fatty liver (PR=1.92; 95% CI:1.03-3.62; p=0.04), while education in DT2 showed a negative association (PR=0.47; 95% CI: 0.36-0.61; p <0,01). Conclusions: Education in DT2 showed an association consistently with the absence of micro and macrovascular complications, suggesting that it is an important preventive factor. We consider it necessary to evaluate the impact of education through appropriate designs.